Initial Public Offerings Short and Long Term Performance of MENA Countries - AlShiab, Mohammad S. (European Scientific Journal, ESJ, 2018)
This study examines a comprehensive set of 162 Middle East and North Africa (MENA) Initial Public Offerings (IPO’s) for the period 2001- 2015, considered the first and most comprehensive data set investigated to date. Results confirmed that IPO performances are mixed among MENA countries classified into three groups. The first group comprises countries whose IPOs over-performed the Benchmark portfolio over the short-run, but underperformed over the long-run. The second group comprises countries where IPOs underperformed the Benchmark portfolio over the following 60 months post-listing date where such underperformance became quite significant over the long-run in comparison to the short-run. The third group comprises countries whose IPOs experienced cyclical performance change from over-performance to under- performance and vice versa. Overall, the IPOs went through cycles of price corrections around the fundamental value over the long term when compared to the short term performance.